Enhanced piezoelectric performance of BiCl3/PVDF nanofibers-based nanogenerators. (26th May 2020) - Chen, Chong; Bai, Zikui; Cao, Yunzheng; Dong, Mingchao; Jiang, Kankan; Zhou, Yingshan; Tao, Yongzhen; Gu, Shaojin; Xu, Jie; Yin, Xianze; Xu, Weilin
Abstract: BiCl3, because of its promoting the formation of β crystal of PVDF and enhancing the conductivity, has drawn increasing attention in the fields of PVDF piezoelectric applications. The high β-phase concentration was achieved from the nanofiber film of PVDF doped with BiCl3, which enhance the piezoelectric power output of the fiber films. Under vertical vibration, the output piezoelectric voltage of BiCl3 /PVDF nanofiber film-based piezoelectric nanogenerator with an optimized ratio of 2 wt% is up to 1.1 V, which is 4.76 times higher than that of pure PVDF fiber piezoelectric nanogenerator. The maximum peak current and power surface density are 2 μA and 0.2 μW cm −2, respectively. The alternating output signals generated from the BiCl3 /PVDF fiber film can be used to charge a capacitor through a bridge rectifier and then light up a red LED. The test method had great influence on the piezoelectric outputs of the piezoelectric device. When a piezoelectric device is impacted by a falling ball, it can produce a voltage output of 38 V. This study shows that the BiCl3 /PVDF nanofiber film based piezoelectric nanogenerator is a promising mechanical energy harvesters for portable electronic and wearable devices. Highlights: The piezoelectric properties of BiCl3 /PVDF nanofiber films were investigated. BiCl3 is beneficial to the formation of β crystals in PVDF nanofiber. The crystal structure and spatial structure of nanofiber film have an important effect on the piezoelectric properties. The output peak voltage of PENG based on BiCl3 /PVDF (2wt%) nanofibers is 4.76 higher than that based on PVDF nanofibers.